2003
DOI: 10.1590/s1415-47572003000200003
|View full text |Cite
|
Sign up to set email alerts
|

Classical and molecular cytogenetic analysis in head and neck squamous cell carcinomas

Abstract: Head and neck carcinomas represent the sixth most frequent type of cancer in the world, and 90% are derived from squamous cells (HNSCC). In this study of 15 HNSCC cases, extensive aneuploidy was detected by G banding in most tumors. The most frequently observed numerical changes involved gain of a chromosome 22, and loss of chromosomes Y, 10, 17, and 19. The most frequent structural alteration was del(22)(q13.1). As compared to G-banding, fluorescence in situ hybridization (FISH) proved to be an effective tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
1
3
0
2
Order By: Relevance
“…However, we have observed a high frequency of monosomy for chromosome 17 in LC patients. Veiga et al also show a high frequency of monosomy 17 by interphase FISH in only three of the tumors [28]. Our cytogenetic results, in addition to other previously reported findings, suggest that losses of chromosome 17 play a role in the pathogenesis of LC.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, we have observed a high frequency of monosomy for chromosome 17 in LC patients. Veiga et al also show a high frequency of monosomy 17 by interphase FISH in only three of the tumors [28]. Our cytogenetic results, in addition to other previously reported findings, suggest that losses of chromosome 17 play a role in the pathogenesis of LC.…”
Section: Discussionsupporting
confidence: 80%
“…These chromosomes may affect the susceptibility to tumors. In other studies, the most frequently observed numerical changes involve the gain (chromosomes 7, 20, and 22) and loss (1, Y, 10, 17, and 19) of chromosomes, and the most common structural rearrangements are deletions of chromosomes 3, 17, and 9 [28,29].…”
Section: Discussionmentioning
confidence: 97%
“…Este porcentaje es muy alto comparado con los publicados por otros autores en diferentes tumores sólidos (25,(35)(36)(37)(38); sin embargo, está dentro del rango informado y concuerda con lo descrito en la literatura en lo referente a que este gen se encuentra alterado en cerca de 50% de todos los canceres en humanos (7,9,10,16,22).…”
Section: Discussionunclassified
“…38 Martin et al previously published a thorough description of specific genetic changes involving autosomes in oral squamous cell carcinoma cases, which included the loss of chromosomal segments 3p, 5q, 7q, 8p, 9p, 11q and 18q in addition to the gain of 3q, 5p, 7p, 8q and 11q …”
Section: X-linked Genes In Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%